Conversion of pine sawdust bio-oil (raw and thermally processed) over equilibrium FCC catalysts - Bertero, Melisa Paola (2013)
A raw bio-oil from pine sawdust, the liquid product from its thermal conditioning and a synthetic bio-oil composed by eight model compounds representing the main chemical groups in bio-oils, were converted thermally and over a commercial equilibrium FCC catalyst. The experiments were performed in a fixed bed reactor at 500 C. The highest hydrocarbon yield (53.5 wt.%) was obtained with the conditioned liquid. The coke yields were significant in all the cases, from 9 to 14 wt.%. The synthetic bio-oil produced lesser hydrocarbons and more oxygenated compounds and coke than the authentic feedstocks from biomass. The previous thermal treatment of the raw bio-oil had the positive effects of increasing 25% the yield of hydrocarbons, decreasing 55% the yield of oxygenated compounds and decreasing 20% the yield of coke, particularly the more condensed coke.